NILAI BUDAYA SEKOLAH DALAM PELAKSANAAN KURIKULUM PENDIDIKAN DI SMK BEKASI - Manaf, Abdul; Omar, Che Mohd Zulkifli Che (Tarbawi, 2018)
This study aims to determine and analyze the school culture values ​​associated with the implementation of the curriculum in the learning process at school. The study was conducted on teachers at SMK in Bekasi. The research used quantitative method with correlation analysis and regression analysis. Data were collected by using instruments on the variables used in the study, ie school culture and educational curriculum. This study found that the school culture aspect has a relationship with the educational curriculum, both academic, socio-cultural and democratic cultures have a positive influence on the school curriculum, so it can be said that the curriculum used in schools will be done well if it has a school culture it is also good that curriculum development in schools requires attention and focus on school culture factors as a way to improve the quality of education curriculum in schools. Keywords. Value of School Culture, Education Curriculum, School, Quality